2022
DOI: 10.1007/s11250-022-03281-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of monochromatic, combined, and mixed light-emitting diode light regimes on growth traits, fear responses, and slaughter-carcass characteristics in broiler chickens

Abstract: This study aims to determine the effects of blue and green monochromatic, blue-green combination, and blue-green mixed led lighting systems on growth, fear, and carcass characteristics of broilers reared in an extensive indoor system. Experimental groups were formed as follows; 1-conventional (incandescent), 2blue, 3-green, 4-blue-green combined (blue for the rst ten days, then green), 5-green-blue combined (green for the rst ten days, then blue), and 6-blue-green intermittent (alternating every 5 minutes) mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(43 reference statements)
0
0
0
Order By: Relevance
“…Correctly selected light color has a positive effect on the well-being of animals and reduces their stress load (Sayin et al 2022). Thus, in hens, a lower concentration of corticosterone in the blood is observed when red light is used during their detention compared to white light (Shi H., 2019;Archer G.S., 2019) or under the influence of ultraviolet radiation (Sobotik et al 2020;House et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correctly selected light color has a positive effect on the well-being of animals and reduces their stress load (Sayin et al 2022). Thus, in hens, a lower concentration of corticosterone in the blood is observed when red light is used during their detention compared to white light (Shi H., 2019;Archer G.S., 2019) or under the influence of ultraviolet radiation (Sobotik et al 2020;House et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike mammals with three monochrome photoreceptors, the hens have four types and distinguish wavelengths from 350 to 700 nm, meaning they also perceive the light in the infrared (longer wavelengths) and ultraviolet (shorter wavelengths) spectra (Barros et al 2020). Correctly selected light color positively affects the hen's welfare and reduces stress (Sayin et al 2022). Thus, a lower concentration of corticosterone in the blood of hens is observed when red light is used during their confinement compared to white light (Shi et al 2019;Archer 2019) or when exposed to ultraviolet radiation (Sobotik et al 2020;House et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there was no discernible difference in carcass quality or yields. Sayin et al (2022) discovered that the intermittent lighting and green-blue combination groups had the worst results for broiler panic reactions. The use of green monochromatic lighting for the first ten days of fattening and blue monochromatic lighting beyond that was found to have a positive impact on growth and slaughter-carcass features.…”
Section: Light Colormentioning
confidence: 99%
“…Moreover, broilers kept under red light settings gained more weight and were preferred by birds to other light hues (Senaratna et al, 2016). Sayin et al (2022) found that the intermittent lighting group and the green-blue combination group had the worst outcomes for the fear reactions of broilers. The use of green monochromatic lighting for the first ten days of the fattening phase and blue monochromatic illumination for the subsequent time was found to have a good impact on growth and slaughtercarcass features.…”
mentioning
confidence: 96%